Scarless surgery for a huge liver cyst: A case report - Kashiwagi, Hiroyuki (Int J Surg Case Rep, 2017)
INTRODUCTION: Symptomatic or complicated liver cysts sometimes require surgical intervention and laparoscopic fenestration is the definitive treatment for these cysts. We performed minimally invasive surgery, hybrid natural orifice transluminal endoscopic surgery (NOTES) without scarring, for a huge liver cyst. PRESENTATION OF CASE: An 82-year-old female presented with a month-long history of right upper abdominal pain. We diagnosed her condition as a huge liver cyst by morphological studies. She denied any history of abdominal trauma. Her serum CEA and CA19-9 were normal and a serum echinococcus serologic test was negative. Laparoscopic fenestration, using a hybrid NOTES procedure via a transvaginal approach, was performed for a huge liver cyst because we anticipated difficulty with an umbilical approach, such as single incision laparoscopic surgery (SILS). Her post-operative course was uneventful and she was discharged from our hospital three days after surgery. Pain killers were not required during and after hospitalization. No recurrence of the liver cyst or bulging was detected by clinical examination two years later. DISCUSSION: A recent trend of laparoscopic procedure has been towards minimizing the number of incisions to achieve less invasiveness. This hybrid NOTES, with a small incision for abdominal access, along with vaginal access, enabled painless operation for a huge liver cyst. CONCLUSION: We report a huge liver cyst treated by hybrid NOTES. This approach is safe, less invasive, and may be the first choice for a huge liver cyst.